HATE SPEECH AGAINST ARTIST LESTY KEJORA'S SON NAMED LESLAR ON SOCIAL MEDIA INSTAGRAM: A FORENSIC LINGUISTIC STUDY - Fenta Pangestika Hayuningtyas (Universitas PGRI Palembang, 2025)
Instagram is a social media platform commonly used to share messages in the form of text, images, audio, or video. The content shared varies depending on the purpose and intentions of the account owner. One such use is the expression of hate speech. This research focuses on hate speech found in the comments made by followers of the artist @lestykejora on a post featuring her newborn son. Many comments were made in text form that aimed to insult and defame the child, Leslar, particularly by mocking his appearance, which resembles his mother, Lesty Kejora. The aim of this study is to examine the forms of illocutionary and perlocutionary speech acts, the presence of taboo expressions, and manifestations of hate speech used by the followers of the @lestykejora account. This study employed a qualitative descriptive method, using data sourced directly from the Instagram account @lestykejora. The findings of the analysis reveal: (1) the dominant forms of hate speech found in the comments are insults and defamation; and (2) the utterances reflect a variety of contextual backgrounds, including physical, psychological, economic, and social aspects.